EFEKTIVITAS DINAS LINGKUNGAN HIDUP DALAM MENGELOLA SAMPAH SEBAGAI UPAYA PERLINDUNGAN TERHADAP LINGKUNGAN - Mustika Wararatna; Rahayu Subekti (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
The goal of this research was to know how effectiveness of trash management based on legislation adopted by the South Tangerang City Environmental Service. The author uses empirical legal methods, using a descriptive qualitative approach. Primary data were gained through conducting field interviews, while secondary data was gathered through a literature review. Considering the study's findings, The South Tangerang City Environmental Service manages garbage in accordance with all applicable relevant laws and regulations, namely Constitution Number 18 of 2018 concerning Garbage Management, South Tangerang City Regional Regulation Number 13 of 2019 concerning Change On Regional Regulation Number 3 of 2013 concerning Trash Management, and Regulation Mayor South Tangerang Number 50 of 2017 concerning Trash Management. However, it is not fully successful in its implementation since the garbage dump is not located in line with the provisions of the garbage dump determination, resulting in environmental contamination in the area surrounding the garbage dump. The inadequate location of the landfill, the residents' lack of awareness of the value of participation in waste management, and limited waste management infrastructure are among the challenges faced by the Environmental Service of South Tangerang City in implementing waste management.